2010
DOI: 10.1002/aoc.1740
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic dehydrogenative coupling of diorganotindihydrides by lanthanide diamide complexes

Abstract: Despite the fact that sterically demanding 1,2-dihydrodistannanes are versatile synthons, their synthesis is typically a tedious, low-yield procedure, which limits synthetic applications. Looking for generally applicable and high-yield routes, we examined the dehydrogenative coupling of sterically crowded diorganotindihydrides. Herein, we report the application of lanthanide diamide-based catalysts (CH 2 ) 3 -1,3-[N(Dipp)] 2 LnBr (Ln=La,Ce,Nd,Dy) to generate polystannanes and distannanes, depending on the size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…[1] Amongst the inorganic Group 14 tetrel elements, it has been shown that catenation leads to species of the general form (R 2 E) n (E = Si, Ge, Sn, and Pb); these materials display novel optoelectronic properties as a result of increasing s-s* conjugation, both as the length of the chains is extended and as the core element becomes heavier. [4,5] Drawn by this challenge and the uncertainty associated with the structures of the metastable halides (SiCl 2 ) n and (GeCl 2 ) n in the solid state, [6] we focused our efforts towards developing an efficient bottom-up synthesis of related oligomers and polymers (ECl 2 ) x (x ! [3] In general, polytetrelanes (R 2 E) n are synthesized under harsh reducing conditions, such as Wurtz coupling, which leads to uncontrolled polymer growth.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[1] Amongst the inorganic Group 14 tetrel elements, it has been shown that catenation leads to species of the general form (R 2 E) n (E = Si, Ge, Sn, and Pb); these materials display novel optoelectronic properties as a result of increasing s-s* conjugation, both as the length of the chains is extended and as the core element becomes heavier. [4,5] Drawn by this challenge and the uncertainty associated with the structures of the metastable halides (SiCl 2 ) n and (GeCl 2 ) n in the solid state, [6] we focused our efforts towards developing an efficient bottom-up synthesis of related oligomers and polymers (ECl 2 ) x (x ! [3] In general, polytetrelanes (R 2 E) n are synthesized under harsh reducing conditions, such as Wurtz coupling, which leads to uncontrolled polymer growth.…”
mentioning
confidence: 99%
“…[3] In general, polytetrelanes (R 2 E) n are synthesized under harsh reducing conditions, such as Wurtz coupling, which leads to uncontrolled polymer growth. [4,5] Drawn by this challenge and the uncertainty associated with the structures of the metastable halides (SiCl 2 ) n and (GeCl 2 ) n in the solid state, [6] we focused our efforts towards developing an efficient bottom-up synthesis of related oligomers and polymers (ECl 2 ) x (x ! 2) in the presence of Lewis basic (LB) hosts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…47 Furthermore in the last decade, organotin dihydrides (R 2 SnH 2 ) have been explored as precursors in the formation of polymeric materials exhibiting a linear backbone of covalently bonded tin atoms. 28,[48][49] However, the solid state structures of organotin hydrides have not been well studied. While alkyl tin hydrides are liquid, the only solid state examples of aryltin hydrides known to date have been isolated by our working group and include mesityl 2 SnH 2 , 28 phenyl 3 SnH, 44 and 2,6-xylyl 3 SnH (8) ( Table 3).…”
Section: Aryltin Hydrides and Bromides (4 8)mentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27] However, solid state examples of trichlorides are limited, and the only aryltin hydride species to have been characterized crystallographically is Mes 2 SnH 2 (Mes = 2,4,6-trimethylphenyl). 28 Very recently, we reported the synthesis, detailed characterization, and DFT studies of novel aryltin chloride and hydride species. 2 Their potential use as starting materials for polyarylstannanes provided the motivation to establish the generation of aryltin trihydrides displaying a hitherto more or less neglected compound class of organotins.…”
Section: Introductionmentioning
confidence: 99%